Riddles as a means of conceptualization of the surrounding world (by the material of Karachay-Balkarian folklore) - Farizat, Gulieva (Kavkazologiya, 2022)
The article is devoted to the research of Karachay-Balkarian riddles in the aspect of displaying objects and phenomena of the natural world, everyday life, the person himself, as well as concepts related to the material and spiritual culture of the ethnic group. The work emphasizes the evalua-tive, descriptive nature of the considered folklore units, identifies the means and ways of concep-tualizing the guessing objects. These include metaphor, metonymy, comparison, antithesis, per-sonification, etc., which can be used both individually and in combination. The analysis of the Ka-rachay-Balkarian riddles allows us to assert that they enshrine, in an allegorical form, a complex of religious, aesthetic, moral and ethical ideas of the ethnos, reflect the features of its worldview, attitude. The study of the works of this genre, their popularization not only contribute to the inter-generational transmission of the cultural and historical experience of the people, but also help to reveal more deeply the specifics of the linguistic picture of the world of the Karachays and Bal-kars. Of no small importance is the pedagogical, educational potential inherent in riddles, that help the development of artistic, figurative, logical thinking of children and adults.